Physiological comparison between non-athletes, endurance, power and team athletes - Degens, H.; Stasiulis, A.; Skurvydas, A.; Statkeviciene, B.; Venckunas, T. (European Journal of Applied Physiology, 2019)
We hypothesized that endurance athletes have lower muscle power than power athletes due to a combination of weaker and slower muscles, while their higher endurance is attributable to better oxygen extraction, reflecting a higher muscle oxidative capacity and larger stroke volume. Endurance (n = 87; distance runners, road cyclists, paddlers, skiers), power (n = 77; sprinters, throwers, combat sport athletes, body builders), team (n = 64; basketball, soccer, volleyball) and non-athletes (n = 223) performed a countermovement jump and an incremental running test to estimate their maximal anaerobic and aerobic power (VO2max), respectively. Dynamometry and M-mode echocardiography were used to measure muscle strength and stroke volume. The VO2max (L/min) was larger in endurance and team athletes than in power athletes and non-athletes (p < 0.05). Athletes had a larger stroke volume, left ventricular mass and left ventricular wall thickness than non-athletes (p < 0.02), but there were no significant differences between athlete groups. The higher anaerobic power in power and team athletes than in endurance athletes and non-athletes (p < 0.001) was associated with a larger force (p < 0.001), but not faster contractile properties. Endurance athletes (20.6%) had a higher (p < 0.05) aerobic:anaerobic power ratio than controls and power and team athletes (14.0-15.3%). The larger oxygen pulse, without significant differences in stroke volume, in endurance than power athletes indicates a larger oxygen extraction during exercise. Power athletes had stronger, but not faster, muscles than endurance athletes. The similar VO2max in endurance and team athletes and similar jump power in team and power athletes suggest that concurrent training does not necessarily impair power or endurance performance.